Multiplying textile lives. Textile collection and recycling in urban Africa - Moritz Kasper; Elmar Stroomer (Agathón)
Worldwide, an estimated 60 billion kilos of textiles and footwear is burned or landfilled every year. Although African countries – including powerhouses such as Kenya and Nigeria – contribute very little to global textile waste, their textile consumption is on the rise. And with increased consumption comes an increased urgency for concepts and designs that utilize textile resources beyond linear lines and singular lives. Africa Collect Textiles was founded in Nairobi, Kenya in 2013, where it has successfully implemented a model for collecting and processing used textiles. Based on fieldwork in Lagos, Nigeria and the extensive experience in Nairobi, this paper will discuss spatial contexts, socio-cultural potentials, and economic modes relevant for adjusting and implementing a textile collection and recycling initiative in urban Africa.